Selección de forrajeras para zona de ladera del norte del Valle del Cauca (Colombia) mediante metodologías participativas - Cárdenas Villarraga, Paula Andrea; Durán Castro, Carlos V.; Roa Velasco, José Ignacio (2007)
During the rainy season (May of 2006) like in dry season (August of 2006), in three sites located on hillsides zones from Bolivar, El Dovio and Sevilla municipalities of Valle del Cauca Department, Colombia, the adaptation process for forage technologies using participative methodologies was evaluated. Open evaluations, absolute evaluations and of preference order evaluation were applied; the last one was statistically analyzed with the methodology of logistical regression. A randomized block design was used, with three replicates for legumes and grasses, respectively. The results of the evaluations by the farmers coincided with that the carried out by technicians. The results of the investigation ranked in the first place the herbaceous legumes, shrub legumes, and grasses, C. brasiliensis, L. leucocephala and hybrid Brachiaria cultivar Toledo, respectively.